Diversity of Soil Filamentous Fungi Influenced by Marine Environment in São Luís, Maranhão, Brazil - Igor Vinícius Pimentel Rodrigues; Katia Regina Assunção Borges; Marcos Antonio Custódio Neto da Silva; Maria do Desterro Soares Brandão Nascimento; Juliano dos Santos; Alexandre Santana Azevedo; Geusa Felipa de Barros Bezerra (The Scientific World Journal)
Introduction. In recent decades, there has been an intensification of environmental problems, which are becoming increasingly critical and frequent due to population growth. Microorganisms, including soilborne fungi, play an essential role in maintaining and balancing the environment. One of the most impacted ecosystems in São Luís, Maranhão, Brazil, is the Jansen Lagoon State Park, an important tourist spot, which has suffered anthropogenic actions such as the dumping of household waste (sewage) in its body of water. As a consequence, these pollutants can accumulate in the adjacent soil, since the body of water is near this substrate. The objectives were to isolate and identify filamentous fungi from the soil of the Jansen Lagoon State Park. Methods. Monthly soil samples were collected and later processed using the modified suspension technique according to Clark (1965). Results. The isolated genera were Aspergillus, Penicillium, Trichoderma, Absidia, and Fusarium. Aspergillus is the fungal genus of greater dominance in the soil of the Jansen Lagoon State Park. Aspergillus niger was the dominant species (37%), followed by A. tamarii (21.6%). Conclusion. The main isolated fungi from the Jansen Lagoon State Park were Aspergillus niger and Aspergillus tamrii. These fungi can be used as biological markers of pollution and as biodegraders and/or bioremediators to improve the area studied.